Even money [compact disc, unabridged] - Francis, Dick (Penguin Audio, 2009)
As bookie Ned Talbot counts his losses after a winning day for gamblers at the Royal Ascot Racecourse, a man comes to him, claiming to be his father. Ned, who's always been told that his parents died when he was a baby, has trouble accepting the man's claims. But when the man is stabbed in the abdomen in the racecourse's parking lot shortly thereafter, Ned rushes to his side. The man's last words force Ned into a race to uncover the truth about his father. However, this race may prove deadly.